The development visions and attitudes towards urban forestry of officials responsible for greening in South African towns. (January 2015) - Gwedla, Nanamhla; Shackleton, Charlie M.
Highlights: The future visions of municipal parks managers were assessed in 24 towns. Managers' visions were largely infrastructure and development orientated. Visions were not related to current street tree density. Street tree density was positively related to town size. There were multiple constraints limiting urban forestry, especially finances. Abstract: The planting and maintenance of trees in public areas of South African towns is the responsibility of local municipalities. Therefore, it is necessary to appreciate the visions and attitudes of municipal officials and decision-makers in charge of such activities for an understanding of the distribution and abundance of trees along streets and in urban green spaces. We hypothesised that the town size and relative wealth and current extent of trees in public places would influence the visions of such officials. We therefore conducted 24 semi-structured interviews with the officials responsible for urban tree planting in 24 towns in the Eastern Cape province, whilst also assessing the abundance of street trees via GIS counts. The density of street trees was variable, ranging from 0.5 to 9.5 trees/ha. There were significantly positive relationships between town size, relative wealth measures and street tree density. Several of the managers did not include environmental issues or trees in vision of the future for their town, although most did. There was no relationship between the managers' visions for the future and attitudes and current street tree density. Most of the managers experienced several constraints in trying to implement their vision, notably a lack of funds for urban forestry, limited space for tree planting in low-cost housing developments, vandalism, and lack of skilled personnel.